Exchange Rate Movements and Inflation Performance : The Case of Italy - Ford, Robert (IMF Working Papers; Working Paper ;, 1995)
This paper presents an empirical model to study the response of wages and prices to movements in the nominal exchange rate. A four-equation model is applied to Italian data to evaluate the response of tradeable goods prices, consumer prices, and wages following the lira's exit from the ERM in the fall of 1992. The model tracks reasonably well the inflation performance of tradeables, especially import prices. But it is argued that structural changes in the labor market contribute to an overprediction of price and wage inflation.